THE CULTURAL POLICY IN THE MULTI-CONFESSIONAL REGIONS OF THE RUSSIAN FEDERATION: JEWISH, CHRISTIAN AND MUSLIM MOTIFS IN THE LEGENDS OF DERBENT - Karina Yuryevna Mosesova; Diana Tekrarovna Hasanova (Современная наука и инновации, 2022)
The article analyzes the foundations of cultural policy in the city of Derbent. In the North Caucasus such cultural and religious leads to positive political consequences: lack of religious hatred and religious toleration. Located at the crossroads of civilizations, Derbent is an example of religious harmony and inter-ethnic dialogue.